HSBM-Produced Zinc Oxide Nanoparticles: Physical Properties and Evaluation of Their Antimicrobial Activity against Human Pathogens - Imen Massoudi; Ridha Hamdi; Ibtisam Ababutain; Ethar Alhussain; Aya Kharma (Scientifica)
This work examines the antibacterial and anticandidal activities of zinc oxide nanoparticles (ZNPs) synthesized by high-speed ball milling (HSBM), for short milling times: 0.5, 1, 1.5, and 2 h. First, ZNPs have been characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, and the Zetasizer analyzer. The HSBM results in semispherical ZNPs with some local agglomeration. We found that nanoparticles decrease in size continuously with milling time until they reach about 84% of their original size after only two hours; at 1000 rpm, HSBM reduces ZNP’s average size by 6 nm/min. As particle size decreases, the X-ray diffracted patterns become broader and less intense while confirming that no phase transformation has occurred, proving HSBM’s effectiveness in synthesizing nanoparticles on a large scale within a short period of time. According to FT-IR analysis, as material sizes change, the polarization charge of the ZNP surface changes as well, creating discrepancies in vibrational frequency, as demonstrated by the shifting of the IR spectra in the 300–600 cm−1 frequency band. Raman responses have also been proven to depend on the particle size. Using the Agar well diffusion method, eleven microorganisms have been tested for the antimicrobial activity of ZNPs. Among the six Gram-negative tested bacteria, S. sonnei showed the largest inhibition zone of about 11.3 ± 0.6 mm with ZNPs measuring 148 nm in size (milled for 2 h), followed by E. coli ATCC 25922. Accordingly, S. aureus was the most susceptible Gram-positive bacteria, with inhibition zone size gradually increasing from 11.8 ± 0.3 mm to 13.5 ± 0.5 mm with decreasing nanoparticle size from 767 to 148 nm, while S. aureus ATCC 25923 was resistant to both milled and unmilled samples. Similar results were seen with candida, all milled ZNPs inhibited C. albicans, followed by C. tropicalis, whereas C. knisei was resistant to all ZNP sizes. In light of microorganism-ZNP interaction mechanisms, the obtained results have been discussed in depth.